Association Between Anxiety and Depression and Nonalcoholic Fatty Liver Disease - Choi, Ji Min; Chung, Goh Eun; Kang, Seung Joo; Kwak, Min-Sun; Yang, Jong In; Park, Boram; Yim, Jeong Yoon (Frontiers in Medicine, 2021)
Backgrounds: Depression and anxiety disorder are frequently seen in patients with nonalcoholic fatty liver disease (NAFLD). However, the associations between mood disorders and NAFLD have not been fully evaluated. In this study, we investigated the relationship between NAFLD and depression or anxiety in a Korean population. Methods: We conducted a retrospective cross-sectional study that included subjects who underwent abdominal ultrasonography and completed a symptom questionnaire for a routine health check-up. NAFLD was diagnosed and graded according to the ultrasonography findings. Depression and anxiety were assessed using the Beck Depression Inventory and State-Trait Anxiety Inventory, respectively. Results: Among the total of 25,333 subjects, the mean age was 47 years (men; 56.2%), and the prevalence rate of NAFLD was 30.9%. In the multivariate analysis, NAFLD showed a significant association with depression [adjusted odds ratio (OR) 1.43 and 95% confidence interval (CI) 1.14-1.80, p = 0.002] in women. Severe NAFLD significantly correlated with state anxiety and trait anxiety [adjusted OR 1.84 and 95% CI 1.01-3.37, p = 0.047 and adjusted OR 2.45 and 95% CI 1.08-4.85, p = 0.018, respectively] in women. Conclusions: There was a higher tendency of women with NAFLD to suffer from depression with increase in steatosis and severe stage of steatosis was significantly associated with anxiety in the female compared to non-NAFLD. Understanding the association between NAFLD and mood disorders may have clinical implications for reducing the prevalence of comorbidities.